Forensic Law in Hypoglycaemia-1 - Derek C Beatty (Studies in Law and Justice, 2023)
Hypoglycaemia, low Blood Glucose BG when BG falls below 3.0mmol/l exhibits Physiological Symptoms of Tremor, Sweating and Hunger, requiring prompt glucose treatment input which if not corrected leads to Confusion, Sensory Disturbance and Behaviour Change at 2.0mmol/l described as Neuroglycopenia. If Blood Glucose BG falls to 1.0mmol/l or 18mg/dl Diabetic Coma is likely to occur leading to unconsciousness and without fast acting glucose severe risk of death. An estimated 600 million patients with Diabetes are thought to exist in the World in 2022 and an estimated 4.5 million in the UK. It is estimated 10% of Diabetes patients are T1D Type 1 Diabetes Insulin Dependent and 90% T2D Type 2 Diabetes Patients Non-Insulin Dependent. Many T2D Patients may require Insulin Treatment several years after diagnosis. Does society really understand the daily burden the diabetes patient faces and the need if things go wrong to provide emergency patient support or the need for A1 Red Alert Emergency support in a hospital, and Paramedic Ambulance support in the Community? This is identified in the UK alone as over 95,000 Emergency Diabetes Hypoglycaemia Calls every year, many of which are potentially avoidable with better understanding and education with family and/or friend witness support.